2022
DOI: 10.1128/aac.00701-22
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus FhdA Transcription Factor Is Important for Mitochondrial Activity and Codon Usage Regulation during the Caspofungin Paradoxical Effect

Abstract: Aspergillus fumigatus is the main etiological agent of aspergillosis. The antifungal drug caspofungin (CSP) can be used against A. fumigatus , and CSP tolerance is observed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…That is, the anticodons of the mitochondrial tRNAome have nucleotides at the wobble site that maximize versatility in wobble base pairing as opposed to maximizing Watson-Crick base pairing with the most frequently used codon within each synonymous codon family. Improving our understanding of Aspergillus mitochondrial tRNA dynamics will not only allow us to better understand translational dynamics within the organelle but recent work has suggested that mitochondrial tRNAs may play a role in antifungal response ( Colabardini et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…That is, the anticodons of the mitochondrial tRNAome have nucleotides at the wobble site that maximize versatility in wobble base pairing as opposed to maximizing Watson-Crick base pairing with the most frequently used codon within each synonymous codon family. Improving our understanding of Aspergillus mitochondrial tRNA dynamics will not only allow us to better understand translational dynamics within the organelle but recent work has suggested that mitochondrial tRNAs may play a role in antifungal response ( Colabardini et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%